Effectiveness of Emotion-Focused Couples Therapy on Sexual Function, Marital Intimacy, and Impulsivity in Women Affected by Marital Infidelity - Nezamalmolki, Mitra; Bahrainian, Seyed Abdolmajid; Shahabizadeh, Fatemeh (Psychology of Woman Journal, 2023)
Objective: One of the most significant factors that can disrupt family health is the breaking of commitment and exclusivity in emotional and sexual relationships, leading to extramarital affairs, also known as marital infidelity. The current study was conducted to determine the effectiveness of Emotion-Focused Couples Therapy (EFCT) on sexual function, marital intimacy, and impulsivity in women affected by marital infidelity.Methods and Materials: This study is a quasi-experimental research with a pre-test, post-test, and three-month follow-up design, accompanied by a control group. The population studied included all women affected by marital infidelity who sought help at the Yarigar counseling centers and the Organic counseling center in Tehran, who had visited these centers in the first six months of the year 2023. According to the counseling centers' officials, the total number of these individuals was 93. The sample studied consisted of 30 women affected by marital infidelity who visited counseling centers in District 2 of Tehran in 2023, selected through purposive sampling and then randomly divided into experimental and control groups. Data were collected using the Marital Intimacy Scale, the Barratt Impulsivity Scale, and the Female Sexual Function Index. In this study, the experimental group underwent 9 sessions of Emotion-Focused Therapy (one 90-minute session per week). Data were analyzed using repeated measures analysis of variance and SPSS software version 22.Findings: The results showed that Emotion-Focused Couples Therapy significantly improved sexual function (F=25.29, P